2020
DOI: 10.1016/j.athoracsur.2019.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Pneumonia Prevention Recommendations After Cardiac Surgery

Abstract: Background. Pneumonia is the most prevalent healthcareassociated infection after coronary artery bypass grafting (CABG), but the relative effectiveness of strategies to reduce its incidence remains unclear. We evaluated the relationship between healthcare-associated infection recommendations and risk of pneumonia after CABG.Methods. Pneumonia prevention practice recommendations were developed based on literature review and analysis of semistructured interviews with key health care personnel across centers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The association between the increased risk of POP and prolonged mechanical ventilation may be explained by the damage to the defense mechanism of the respiratory system, and preforming extubation as early as possible may be a feasible strategy for reducing POP. [33][34][35] In addition to the prediction of individualized POP risk, the nomogram model may play an important role in risk stratification and clinical prevention. Several preventive measures, such as subglottic secretion drainage and preoperative chlorhexidine mouthwash, may be helpful for the reduction of POP risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the increased risk of POP and prolonged mechanical ventilation may be explained by the damage to the defense mechanism of the respiratory system, and preforming extubation as early as possible may be a feasible strategy for reducing POP. [33][34][35] In addition to the prediction of individualized POP risk, the nomogram model may play an important role in risk stratification and clinical prevention. Several preventive measures, such as subglottic secretion drainage and preoperative chlorhexidine mouthwash, may be helpful for the reduction of POP risk.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we did not incorporate these factors into our multivariate analysis as they were postoperative variables and were not available early. The association between the increased risk of POP and prolonged mechanical ventilation may be explained by the damage to the defense mechanism of the respiratory system, and preforming extubation as early as possible may be a feasible strategy for reducing POP 33–35 …”
Section: Discussionmentioning
confidence: 99%
“…There is a significant correlation between nutritional status and the prognosis of critically ill children ( 24 , 25 ), which was mainly reflected in this study by shorter duration of mechanical ventilation and lower incidence of pneumonia in the intervention group. This is because earlier extubation prevents pneumonia ( 26 ); it is also possible that children with poor nutritional status have a poor inflammatory response and are therefore more susceptible to pneumonia, as other studies have confirmed ( 27 , 28 ). However, the findings on whether high-energy nutrition shortens the length of hospital stay have not been uniform.…”
Section: Discussionmentioning
confidence: 97%
“…Some other measures have also been reported to be effective in prevention and treatment, including lung protective ventilation management, alveolar recruitment maneuvers, early mobilization and progressive ambulation, elevation of the head end and semi-recumbent positioning, sedation vacation and the use of a weaning protocol, early extubation, strict changes of ventilatory circuit tube, appropriate cuff pressure control, use of non-invasive ventilation, proper use of tracheostomy, enteral feeding, selective digestive decontamination, peptic ulcer disease prophylaxis, silver-coated endotracheal tubes, microbiological surveillance, and deep vein thrombosis prophylaxis (104)(105)(106)(107)(108)(109). In recent years, some prevention care bundles and prevention checklists which consist a series of rationalized measures have been developed and validated to be effective and convenient in preventing POP and shortening the duration of mechanical ventilation.…”
Section: Other Interventionsmentioning
confidence: 99%